Strategic Measurement Method Using Balanced Scorecard Approach at The North Minahasa District Health Office - Joice L.M. Katuuk; Bernhard Tewal; James Massie; Victor Lengkong (International Journal of Applied Business and International Management, 2019)
The purpose of this study is to identify and analyze a series of processes to realize the strategy objectives through strategic measurement using the Balanced Scorecard approach at the North Minahasa District Health Office. The research method used was qualitative with a case study design. The results show that the Balanced Scorecard approach as a strategic management tool can improve the quality of strategy implementation, when it can clarify the size of its strategic performance. This case study contributes to the current state of knowledge and local government regarding the development and implementation of the Balanced Scorecard in the future to local governments that intend to implement it. For further research, the trial of the application of the Balanced Scorecard to local governments is an important strategic issue